Speciation of Iron, Nickel and Cobalt in the Anaerobic Biodegradation of Rice Straw [Especiación de Hierro, Níquel y Cobalto en la Biodegradación Anaerobia de la Paja de Arroz] - Montalvo-Martinez, S (Universidad de Antioquia, 2021)
The bioavailability of Fe, Ni and Co and its impact on the mono-digestion of rice straw with addition of a natural nutrient source were assessed. The chemical forms and the degree of bioavailability of Fe, Ni and Co were investigated in two reactors during 311 days of experimentation at 37°C. The reactor (R2) was supplemented with 1 g/L of mineral once a week. The control reactor R1 was limited in mineral during the study. The greatest methane yield of 238 mL/g VS was obtained with mineral supply with an increment of 45% respect to reactor without metals (164 mL/g VS). The sequential extraction confirmed that 70, 88 and 75% of Fe, Ni and Co were mainly in bioavailable forms (interchangeable and carbonate), respectively, with mineral supply in R2. Fe and Co were mainly associated to the carbonate and oxidizable fractions (43% and 41% respectively), while the Ni concentrations were not detected during the experimentation. As a result, the methane yield in R2 increased by 45%, with a potential bioavailability (Ni > Co > Fe) higher compared to control reactor (Co > Fe). Trace elements deficit in R1 result in the reduction of metal-binding forms until the end of experiment, with a negative impact on methanogenic community. © 2021,Revista Facultad de Ingenieria. All Rights Reserved.